(untitled) (Mustansiria Dental Journal, 2018)
Amoxicillin have been widely described by dentists in Iraq, especially in treatment of periodontal and other oral bacterial infections. Amoxicillin is the 4-hydroxy analogue of ampicillin and is used in a similar variety of susceptible infections. Clinical pharmacology of amoxicillin in saliva was not sufficiently studied on normal subjects or patients required amoxicillin treatment. The purpose of this study is to determine the amoxicillin concentration in saliva by using an efficient, low cost and reproducible method. The obtained results from high performance liquid chromatography (HPLC) method revealed that salivary concentration of amoxicillin ranged from 0.22 to 0.44 μg. / ml. The HPLC method was proved to be a successful method for monitoring the amoxicillin in saliva with a detection limit reached to 0.08 μg/ml. It is important to suggest further study to know the therapeutic effect of amoxicillin through saliva against certain oral lesions.